2003
DOI: 10.1210/jc.2003-030486
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteoprotegerin as a Determinant of Bone Metabolism in a Longitudinal Study of Human Pregnancy and Lactation

Abstract: Osteoprotegerin (OPG) is a soluble decoy receptor that inhibits bone resorption by binding to receptor activator of nuclear factor kappa B ligand. Murine studies suggest that OPG is elevated in pregnancy, but its role in human pregnancy is unknown. We evaluated the relationship among OPG, bone turnover, and bone density in a longitudinal study of planned human pregnancy and lactation (n = 17; age, 20-36 yr). Samples were collected before conception; at 16, 26, and 36 wk gestation; and at 2 and 12 wk postpartum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…Previous studies suggest that maternal levels of OPG gradually increase throughout gestation and are significantly elevated immediately before delivery [26][27][28][29] . The tissue source of OPG in pregnant women is unknown [29] ; however, the rapid postpartum OPG decline in maternal serum [28,29] , the documented expression of OPG in placental tissue [12] and the lower serum OPG levels in neonates compared with their mothers -as reported in the present study -point to a placental origin of OPG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that maternal levels of OPG gradually increase throughout gestation and are significantly elevated immediately before delivery [26][27][28][29] . The tissue source of OPG in pregnant women is unknown [29] ; however, the rapid postpartum OPG decline in maternal serum [28,29] , the documented expression of OPG in placental tissue [12] and the lower serum OPG levels in neonates compared with their mothers -as reported in the present study -point to a placental origin of OPG.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one could assume that OPG levels in neonates reflect maternal OPG levels or are of placental origin. However, it has been shown that OPG in umbilical cord blood was not markedly elevated compared with that in maternal serum, suggesting that the fetus is not a source of OPG in maternal circulation [15]. Human placental microvessels are characterised by endothelial paracellular junctions that are fairly tight and generally impermeable to macromolecules larger than 40,000 Da [39], while OPG is a monomer with a molecular weight of 60,000 Da [40].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary atherosclerosis is associated with high serum OPG levels in humans, but the exact mechanisms are not yet elucidated [9,10,11,12,13]. Currently, there is little information regarding OPG and RANKL concentrations and their potential role in the human fetus and neonate [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…The changes measured in serum may in fact underestimate changes occurring in bone because of non-skeletal sources of OPG and RANKL production that may mask what is occurring in bone tissue. Moreover, OPG is expressed in several tissues other than bone, including lung, heart, kidney and placenta [14].…”
Section: Discussionmentioning
confidence: 99%